Mastering English literature - Gill, Richard (Palgrave master series, 2006)
The third edition of this book has been completely rewritten and provides a comprehensive introduction to literary study, offering advice on approaches to the main areas of literature - the novel, drama and poetry. Easily accessible and clearly explained, Mastering English Literature is an essential text designed to help readers appreciate the various ways in which literature engages us.